Formulation and Evaluation of Herbal Antioxidant Tablets of Urtica Dioica Extract - Timalsina, Jony; Dhukuchhu, Sunena; Dhukuchhu, Jina; Bhattarai, Alisha; Shrestha, Rajan; Gyawali, Rajendra (Journal of Nepal Chemical Society, 2024)
This study explores the formulation and assessment of herbal antioxidant tablets derived from Urtica dioica (stinging nettle) extracts for arthritis and osteoarthritis treatment. Various extraction methods were compared, revealing that 100% dehydrated ethanol at 45 degrees Celsius for four hours in a Soxhlet apparatus resulted in an 89% phenolic extraction. Although ethyl acetate yielded the highest phenolic extract (187%), its toxicity led to the selection of ethanol for further extraction. The Folin-Ciocalteu method determined the total phenolic content. The DPPH assay demonstrated positive antioxidant activity of the Urtica dioica ethanolic extract, with an IC50 value of 37.5761201 μg/mL, compared to the standard ascorbic acid with an IC50 value of 21.23506 μg/ml. Herbal tablets were formulated using the direct compression method. The findings highlight the potential of Urtica dioica extracts as effective herbal antioxidants for arthritis and osteoarthritis treatment. This research enhances our understanding of natural remedies and their therapeutic applications. Future investigations should delve into the clinical efficacy and safety of these herbal antioxidant tablets, paving the way for their potential integration into clinical settings. This study contributes valuable insights into the development of alternative therapies for managing arthritic conditions, emphasizing the importance of exploring nature’s remedies in healthcare.